O crime como método: um estudo da literatura policial na obra de Mayrant Gallo - Nunes, Lidiane Carvalho (2014)
In this dissertation, we analyze the short crime stories by Mayrant Gallo ─ one of the most productive writers from Bahia presently ─ trying to demonstrate the theme of crime as a metaphor of the world we live in, which is often violent and corrupt. In the work of the author in question ─ as well as in the work of many others crime fiction writers ─, we show clearly that the representation of the criminal universe is a method or a means of making the reader reflect on things more widely than the simple “who killed” questioning. We aim to demystify the ideia very widespread among literary critics that crime fiction is a “minor genre”. In this regard, we discuss the characteristics, similarities and differences between its types: detective fiction, noir and “action” fiction. This last type, although practiced by writers like Edgar Allan Poe e Jorge Luis Borges, for example, had its terminology coined only in 2005, by Mayrant Gallo, who is also a teacher and a crime fiction theorist, a genre which has been insufficiently researched in the academy.